1996
DOI: 10.1097/00006454-199601000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of one vs. two injections of Oka/Merck varicella vaccine in healthy children

Abstract: Administration of a one- or two-dose regimen of the live Oka/Merck varicella vaccine (VARIVAX) is immunogenic and is generally well-tolerated in healthy children 1 to 12 years old. Antibody to varicella persists in > 99% of vaccinees 1 year after vaccination regardless of a one- or two-dose regimen. Long-term follow-up studies of this cohort of children may determine whether a two-dose regimen offers superior protection against chickenpox.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 10 publications
1
29
1
Order By: Relevance
“…Injection site pain was reported in <10% of subjects in each group after both doses. In contrast to previous studies [24,27,32], no increase in local reactions was observed from dose 1 to dose 2 in either group. Local symptoms of a high intensity were rare.…”
Section: Safety and Reactogenicitycontrasting
confidence: 99%
“…Injection site pain was reported in <10% of subjects in each group after both doses. In contrast to previous studies [24,27,32], no increase in local reactions was observed from dose 1 to dose 2 in either group. Local symptoms of a high intensity were rare.…”
Section: Safety and Reactogenicitycontrasting
confidence: 99%
“…In June 2006, the Advisory Committee on Immunization Practices recommended a routine 2-dose schedule for varicella vaccination, to improve vaccine-induced immunity and the control of varicella and to minimize the burden of breakthrough varicella disease [24]. Clinical studies have suggested that a second dose of varicella vaccine could provide increased protection against varicella, thus reducing the risk of breakthrough disease by 3-fold [25][26][27]. As this new vaccine schedule is implemented, it will be important to continue to monitor changes in varicella epidemiology, with a focus on varicella disease among vaccinated persons and the agespecific rates of serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine virus propagates in varicella-naïve persons at the injection site, as evidenced by occasional local skin lesions containing vaccine virus. Vaccination must also occasionally cause a viremia, as indicated by the appearance of VZV in skin lesions distant from the injection site in a minor proportion of vaccinees (Ngai et al 1996). Vaccine strain VZV also gains access to peripheral ganglia, either by ascending the peripheral nerve that innervates the injection site or as a consequence of viremia, as evidenced by the subsequent late appearance of HZ caused by Oka strain VZV (Galea et al 2008;Levin et al 2008a).…”
Section: Varicella Vaccinementioning
confidence: 99%